Intervensi Nonfaramakologik untuk Mengurangi Cemas dalam Meningkatkan Kualitas Hidup ODHA - Sitti Shoimatul A; Agung Waluyo; Sri Yona (Jurnal Keperawatan Silampari, 2022)
This study aims to explore non-pharmacological interventions that can reduce anxiety in improving the quality of life of ODHA. The research method used is a search in the online databases of PubMed, Scopus, ScienceDirect, Wiley Online, and Embase. The results of the research data were analyzed and summarized based on the effect of the intervention given on anxiety. There are three themes of non-pharmacological interventions such as yoga, reiki and massage that can have an anxiety-reducing effect. In conclusion, non-pharmacological interventions can reduce anxiety, ODHA who have a high anxiety score will have an impact on their quality of life. Non-pharmacologic interventions such as yoga, massage and reiki can be applied to people living with HIV in reducing anxiety to improve their quality of life. Keywords: Anxiety, Quality of life, ODHA